Swiss ball training versus stable surface training for the treatment of low back pain in male judo athletes - Monroy Anton, A. J.; Rodriguez Rodriguez, B.; Lopez Jimenez, D. (Archives of Budo, 2015)
Background and Study Aim: Between 60% and 80% of the population suffers from low back pain at some point in their lives. This disease is commonly observed in judo, with a prevalence of around 35%. Therefore, any instrument, program or training method for the treatment of this disease is very important. Apparently, unstable surface training can be effective in reducing low back pain. However, there are not many studies that have been conducted in this regard, and the few existing ones have not opted for any particular training method. The purpose in this study is knowledge about the effect on low back pain of two different training programs, one using Swiss ball and the other with stable surface. Material and Methods: Thirty-six active volunteers, all of them judo athletes, participated in the study. They were randomly assigned to either the training group (exercising on a Swiss ball) or the control group (training on stable surface). Pain intensity was measured at the beginning and at the end of the 8 weeks in both groups by the Spanish version of the Roland Morris Disability Questionnaire (RMDQ). Results: The results of paired t test showed a significant decrease in RMDQ after treatment in both groups compared with before treatment (p<0.001), while the ANCOVA revealed no significant differences among groups on the post measurement score of RMDQ, with pre-treatment scores as the covariate. Conclusions: The training on unstable surfaces does not provide any significant improvement versus training on stable surfaces and might be at least as good as training on a Swiss ball in the reduction of low back pain for judo athletes.